Question
upstudy study bank question image url

1. Solve for \( x \) and \( y \) : (a) \( 3 x-14 y=0 \) and \( x-4 y+1=0 \) (b) \( x+y=8 \) and \( 3 x+2 y=21 \) (c) \( y=2 x+1 \) and \( x+2 y+3=0 \) (dd) \( \frac{a}{2}+b=4 \) and \( \frac{a}{4}-\frac{b}{4}=1 \) (e) \( \frac{1}{x}+\frac{1}{y}=3 \) and \( \frac{1}{x}-\frac{1}{y}=11 \)

Ask by John Pollard. in South Africa
Feb 18,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

Solutions for the systems of equations are as follows: (a) \( x = -7 \), \( y = -\frac{3}{2} \) (b) \( x = 5 \), \( y = 3 \) (c) \( x = -1 \), \( y = -1 \) (dd) \( a = \frac{16}{3} \), \( b = \frac{4}{3} \) (e) \( x = \frac{1}{7} \), \( y = -\frac{1}{4} \)

Solution

Sign in to Unlock Answers for Free!

A Learning Platform Trusted by Millions of Real Students and Teachers.

star-icon Unlock

Answered by UpStudy AI and reviewed by a Professional Tutor

Beyond the Answer

Let's solve each pair of equations step by step: (a) From \( 3x - 14y = 0 \), we can express \( x \) in terms of \( y \): \( x = \frac{14}{3}y \). Substituting this into the second equation \( x - 4y + 1 = 0 \): \( \frac{14}{3}y - 4y + 1 = 0 \) This simplifies to: \( \frac{14}{3}y - \frac{12}{3}y + 1 = 0 \) \(\frac{2}{3}y + 1 = 0 \Rightarrow y = -\frac{3}{2} \). Substituting \( y \) back into \( x = \frac{14}{3}y \): \( x = \frac{14}{3}(-\frac{3}{2}) = -7 \). So, \( x = -7, y = -\frac{3}{2} \). (b) From \( x + y = 8 \), we can express \( y \): \( y = 8 - x \). Substituting this into the second equation \( 3x + 2y = 21 \): \( 3x + 2(8 - x) = 21 \) This simplifies to: \( 3x + 16 - 2x = 21 \Rightarrow x + 16 = 21 \Rightarrow x = 5 \). Substituting \( x \) back into \( y = 8 - x \): \( y = 8 - 5 = 3 \). So, \( x = 5, y = 3 \). (c) From \( y = 2x + 1 \), substitute \( y \) into the second equation \( x + 2y + 3 = 0 \): \( x + 2(2x + 1) + 3 = 0 \) This expands to: \( x + 4x + 2 + 3 = 0 \Rightarrow 5x + 5 = 0 \Rightarrow 5x = -5 \Rightarrow x = -1 \). Substituting \( x \) back into \( y = 2x + 1 \): \( y = 2(-1) + 1 = -2 + 1 = -1 \). So, \( x = -1, y = -1 \). (d) From \( \frac{a}{2} + b = 4 \), express \( b \): \( b = 4 - \frac{a}{2} \). Substituting into the second equation \( \frac{a}{4} - \frac{b}{4} = 1 \): \( \frac{a}{4} - \frac{1}{4}(4 - \frac{a}{2}) = 1 \). This simplifies to: \( \frac{a}{4} - 1 + \frac{a}{8} = 1 \). Multiplying through by 8 to eliminate the fractions: \( 2a - 8 + a = 8 \Rightarrow 3a - 8 = 8 \Rightarrow 3a = 16 \Rightarrow a = \frac{16}{3} \). Substituting \( a \) back to find \( b \): \( b = 4 - \frac{8}{3} = \frac{12}{3} - \frac{8}{3} = \frac{4}{3} \). So, \( a = \frac{16}{3}, b = \frac{4}{3} \). (e) From \( \frac{1}{x} + \frac{1}{y} = 3 \), multiply through by \( xy \): \( y + x = 3xy \). From \( \frac{1}{x} - \frac{1}{y} = 11 \), multiply through by \( xy \): \( y - x = 11xy \). Now we have the two equations: 1) \( y + x = 3xy \) 2) \( y - x = 11xy \) Adding both equations: \( 2y = 14xy \Rightarrow y = 7xy \) and substituting into either equation yields: Set \( y = 7xy \Rightarrow 1 = 7x \Rightarrow x = \frac

Related Questions

Latest Algebra Questions

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy